The effects of AI on media business: Anxiety, Quality and Creativity - Dariusz RAŚ; Anna PRUSAK; Seweryn PUCHAŁA (Communications of International Proceedings, 2024)
The aim of this paper is to deliberate on the effects of extensive use of AI technology in the contemporary media market. It focuses on three relevant issues, namely: Automation Anxiety (AA), Quality Journalism (QJ) and Creative Journalism (CJ). The motive behind the study emerged from the increasing use of new technologies in media and entertainment businesses, and at the same time, the fact that more and more employees express concerns about their future, feeling “anxious” about their jobs. The study was based primarily on the literature review. The authors provided their own elaboration over the state-of-the-art knowledge and came up with a conceptual model combining key issues around the use of AI in media businesses.  The implications of social communication, media and journalism were provided by discussing benefits of AI for media outlets and journalists, and the importance of ethics in light of the above has been also highlighted.
Keywords: artificial intelligence (AI; automation anxiety (AA); quality journalism; creative journalism; media business